Special Focus: Teaching 20th and 21st Century Literature - Kathleen Antonioli (Studies in 20th & 21st Century Literature, 2026)
Introduction for the Special Focus of STTCL 50.1: Teaching 20th and 21st Century Literature.
Keywords: teaching; literature